2020
DOI: 10.1186/s40478-020-00956-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and dynamic studies of the endosomal compartment in Down syndrome

Abstract: Enlarged early endosomes have been visualized in Alzheimer's disease (AD) and Down syndrome (DS) using conventional confocal microscopy at a resolution corresponding to endosomal size (hundreds of nm). In order to overtake the diffraction limit, we used super-resolution structured illumination microscopy (SR-SIM) and transmission electron microscopies (TEM) to analyze the early endosomal compartment in DS. By immunofluorescence and confocal microscopy, we confirmed that the volume of Early Endosome Antigen 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 88 publications
(113 reference statements)
4
34
1
Order By: Relevance
“…Endosomal pathology has been also shown in human DS neurons, in neurons of DS mouse models, and in human DS fibroblasts [ 188 , 189 , 190 , 191 , 192 ]. Several evidence and emerging hypotheses suggest that triplicated genes, such as ITSN1 and SYNJ1, are implicated in triggering the abnormalities of endolysosomal pathway [ 193 ].…”
Section: Stress Responses In Down Syndrome Brainmentioning
confidence: 99%
“…Endosomal pathology has been also shown in human DS neurons, in neurons of DS mouse models, and in human DS fibroblasts [ 188 , 189 , 190 , 191 , 192 ]. Several evidence and emerging hypotheses suggest that triplicated genes, such as ITSN1 and SYNJ1, are implicated in triggering the abnormalities of endolysosomal pathway [ 193 ].…”
Section: Stress Responses In Down Syndrome Brainmentioning
confidence: 99%
“…In agreement, other reports have noted a ~18% increase in the size of EEA1+ vesicles without significant differences in the number of this type of vesicles. Enlargement of lysosomes in fibroblasts from individuals with trisomy 21 has also been reported 45,47 . Of note, the average size of LAMP1+ vesicles in fixed cells with trisomy 21 was smaller.…”
Section: Discussionmentioning
confidence: 83%
“…Alterations in the morphology of endosomes have been described in primary fibroblasts, neurons, peripheral blood mononuclear cells, and lymphoblastoid cell lines from individuals with Down syndrome 36,37,[43][44][45] . Our comparative morphological analysis of IgG+ vesicles and subcellular compartments in fibroblasts with and without trisomy 21 revealed enlargement of subcellular organelles from the endosomal pathway, resembling the "traffic jam" previously described for DS and Alzheimer's disease 45,46 . We found that trisomic cells have larger EEA1+ endosomes (~12%), Rab11+ endosomes (~24%), and lysotracker-stained lysosomes (28%) than diploid cells (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations